Gene therapy approaches for equine osteoarthritis - Thampi, Parvathy; Samulski, R. Jude; Grieger, Joshua C.; Phillips, Jennifer N.; McIlwraith, C. Wayne; Goodrich, Laurie R. (Frontiers in Veterinary Science, 2022)
With an intrinsically low ability for self-repair, articular cartilage injuries often progress to cartilage loss and joint degeneration resulting in osteoarthritis (OA). Osteoarthritis and the associated articular cartilage changes can be debilitating, resulting in lameness and functional disability both in human and equine patients. While articular cartilage damage plays a central role in the pathogenesis of OA, the contribution of other joint tissues to the pathogenesis of OA has increasingly been recognized thus prompting a whole organ approach for therapeutic strategies. Gene therapy methods have generated significant interest in OA therapy in recent years. These utilize viral or non-viral vectors to deliver therapeutic molecules directly into the joint space with the goal of reprogramming the cells' machinery to secrete high levels of the target protein at the site of injection. Several viral vector-based approaches have demonstrated successful gene transfer with persistent therapeutic levels of transgene expression in the equine joint. As an experimental model, horses represent the pathology of human OA more accurately compared to other animal models. The anatomical and biomechanical similarities between equine and human joints also allow for the use of similar imaging and diagnostic methods as used in humans. In addition, horses experience naturally occurring OA and undergo similar therapies as human patients and, therefore, are a clinically relevant patient population. Thus, further studies utilizing this equine model would not only help advance the field of human OA therapy but also benefit the clinical equine patients with naturally occurring joint disease. In this review, we discuss the advancements in gene therapeutic approaches for the treatment of OA with the horse as a relevant patient population as well as an effective and commonly utilized species as a translational model.